2015
DOI: 10.1080/01459740.2015.1091819
|View full text |Cite
|
Sign up to set email alerts
|

The Precariousness of Public Health: On Tuberculosis Control in Contemporary France

Abstract: Through an ethnographic exploration of tuberculosis control in one of France's poorest regions, Seine-Saint-Denis, I interrogate the relationships between public health planning and interventions in conditions of multiple precarity. I show that the encounter between the feasible and the fantastic in the realm of public health generates feelings of absurdity and futility among medical professionals, characteristic of disease control in the precarious present. Precarity is neither a social and economic condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In addition to the ability to identify scenarios with a higher propensity for treatment non-adherence, these findings highlight that conditions of social and economic development also affect the conditions of tuberculosis treatment among the population of Rio de Janeiro. Kehr (2016) [ 31 ] observed that tuberculosis control, including ensuring full treatment of marginalized populations, depends not only on the availability of drugs and the functioning of health services, but also on social and political inclusion. Mason (2016) [ 32 ] reaffirmed the importance of social science and medical anthropology concepts in the understanding of tuberculosis, stressing the need to recognize the complexity of the social, economic, cultural, geographic, and political aspects involved in the control of tuberculosis[ 33 ], In an ethnographic study of the abandonment of tuberculosis treatment among Bolivians Aymara, Greene (2004) recognized that in addition to cultural differences, social determinants of access to treatment can reduce tuberculosis control.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the ability to identify scenarios with a higher propensity for treatment non-adherence, these findings highlight that conditions of social and economic development also affect the conditions of tuberculosis treatment among the population of Rio de Janeiro. Kehr (2016) [ 31 ] observed that tuberculosis control, including ensuring full treatment of marginalized populations, depends not only on the availability of drugs and the functioning of health services, but also on social and political inclusion. Mason (2016) [ 32 ] reaffirmed the importance of social science and medical anthropology concepts in the understanding of tuberculosis, stressing the need to recognize the complexity of the social, economic, cultural, geographic, and political aspects involved in the control of tuberculosis[ 33 ], In an ethnographic study of the abandonment of tuberculosis treatment among Bolivians Aymara, Greene (2004) recognized that in addition to cultural differences, social determinants of access to treatment can reduce tuberculosis control.…”
Section: Discussionmentioning
confidence: 99%
“…It runs speedily in because of hunger’. Ezra’s take on the dominant approaches to TB that favour medically orientated strategies such as testing, treatment and preventative treatment was that they are short-sighted and will not address the ‘social and political precarities that enable TB to prosper’ (Kehr, 2016, p. 383):We can keep on trying with our medicine… medicine will run out and the sickness will still remain. We can continuously fund many millions, and money will run out but this sick will still remain because this is an island [and] nobody is eating.…”
Section: Findings: Signposts Of the Structural Conditions In Which Tb...mentioning
confidence: 99%
“…Cuts in medical services, rising user fees and the triage of those worthy or unworthy for ever more expensive treatments are domains in which the neoliberal feedback loop leads to the collapse of categorical distinctions between South and North, here and elsewhere, own and other, despite their stubborn solidity and their easy instrumentalisation for powerful politics of differentiation and exclusion, especially in the domain of migrant care (Kehr, 2016). In Berlin, renewed concerns with tuberculosis oscillate between an ongoing faith in techno-medical progress and public welfare and a parallel fear of social and economic decay that might threaten the slowing of disease incidence or even inverse the tendency.…”
Section: Precarisation Of Tuberculosis Controlmentioning
confidence: 99%